Nondestructive monitoring of subsurface damage progression in concrete columns damaged by earthquake loading. (1st May 2016) - Freeseman, Katelyn; Khazanovich, Lev; Hoegh, Kyle; Nojavan, Alireza; Schultz, Arturo E.; Chao, Shih-Ho
Highlights: A full-scale RC column was subjected to simulated earthquake loading. Testing was supplemented using a shear wave ultrasound array system. Reflectivity reconstructions showed damage before it was visible at the surface. Quantitative characteristics were developed to assess damage progression. The proposed method is nondestructive and requires only one-sided access. Abstract: The assessment of the structural integrity of infrastructure after extreme events is an important application of nondestructive technology. Advancements in elastic wave-based methods in recent years have allowed for productive and accurate quantitative analysis which was previously lacking. In this study, ultrasonic array measurements coupled with a modified signature analysis method were implemented for damage detection purposes. Full-scale testing of a reinforced concrete column subjected to simulated earthquake loading was tested using ultrasound nondestructive testing at various stages of loading. A signature analysis technique was adapted to create improved reconstructions and was coupled with a quantitative analysis incorporating Pearson's correlation coefficient. The results demonstrated the ability to detect internal damages and defects prior to appearance on the surface using one-sided access, showing promise for health monitoring applications.